Discrete wavelet transform and support vector machines algorithm for fault locations on single circuit transmission line - Kunadumrongrath, K.; Ngaopitakkul, A. (My University, 2012)
This paper proposes a technique using discrete wavelet transform (DWT) and support vector machines (SVM) for fault location on single circuit transmission lines. The ATP/EMTP is used to simulate fault signals. The mother wavelet daubechies4 (db4) is employed to decompose high frequency component from these signals. The first peak time in first scale capable of detecting fault of each bus is used as input pattern for the training pattern. It is shown that the proposed technique gives satisfactory results.
Keywords: Fault Location; Support Vector Machines; Transmission Line; Wavelet Transform